Towards a healthy and safe jellyfish snack: preliminary assay with allergic patients - Morais, Zilda (2016)
Poster presented at the First International Congress of CiiEM: From Basic Sciences to Clinical Research, 27-28 November 2015, Egas Moniz, Caparica, Portugal.